PENGARUH KOMUNIKASI INTERPERSONAL MAHASISWA DAN DOSEN PEMBIMBING SKRIPSI TERHADAP GEJALA STRES MAHASISWA DALAM MENYUSUN SKRIPSI - Puput Citra Yulia; Henny Afrianti; Vethy Octaviani (Professional: Jurnal Komunikasi dan Administrasi Publik, 2015)
This study was conducted to determine the influence of interpersonal communication between students and the thesis supervisor students in the stress symptoms thesis. Based on initial observations on Communication department students of Dehasen University year 2010, of the 62 students who have submitted a title and run the thesis counseling process, only 29 students managed to reach the stage of proposal examination. One of the obstacles faced by students is the lack of good interpersonal communication so that interpersonal relationships are not well established. This research is a quantitative descriptive. Sample set by using purposive sampling of the students of Communication Department who were working on thesis, that is 38 students. The results showed that interpersonal communication between students and thesis supervisor has not been effective so that the discussion does not go well. The ineffectiveness of communication activities lead students to experience stress symptoms so that interfere the completion of thesis writing.Keywords: Interpersonal Communication, Stress